Guidance of Teaching English to Young Learners (TEYL) for Early Childhood Education Teachers at Ad Dhuha Kindergarten of Jember - Ahmad Jazuly; Ninuk Indrayani (Linguistic, English Education and Art (LEEA) Journal, 2018)
This study aims to find out how the application of English teaching guidance to young students (TEYL) for early childhood education (PAUD). This study on community service has been implemented in TK Ad Dhuha Kabupaten Jember, East Java. Community service is done because of the unity of National Park commemorate National Education Day (NED).The method used in this research is observation, interview, and presentation between writer and audience about the technique of guidance on the implementation of teaching English to young students (TEYL) for teachers of Early Childhood Education in Ad Dhuha Jember Kindergarten. There are 24 teachers collected from 4 kindergarten schools consisting of 1 male and 23 female. The results of this study are: (1) the writer knows the teacher's ability to teach English in Ad Dhuha kindergarten, (2) The writer knows the teaching-learning method used by teachers for their children, (3) The teachers can develop teaching methods that have been learned during the training in community service at Ad Dhuha kindergarten. Keywords: early childhood education teachers, kinds of Teaching EYL, ad Dhuha Kindergarten.